The drying kinetics of seeded grape in solar dryer with PCM-based solar integrated collector - Cakmak, Gulsah; Yildiz, Cengiz (Elsevier, 2011)
This paper presents a novel type of dryer for experimentally evaluating the drying kinetics of seeded grapes. In the developed drying system, it has been particularly included an expanded-surface solar air collector, a solar air collector with phase-change material (PCM) and drying room with swirl element. An expanded-surface solar air collector has been used to achieve high heat transfer and turbulence effect whiles a solar air collector with PCM has been used to perform the drying process even after the sunset. On the other hand, the swirl elements have been located to. give the swirl effect to air flow in drying room. These advantages make the proposed novel system a promising dryer in that lower moisture value and less drying time. The drying experiments have been carried out simultaneously both under natural conditions and by the dryer with swirl flow and without swirl flow at three different air velocities. The obtained moisture ratio values have been applied to six different moisture ratio models in the literature. The model having the highest correlation coefficient (R) and the lowest Chi-square (chi(2)) value has been determined as the most relevant one for each seeded grape drying status. (C) 2010 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Solar collector; Seeded grape; Drying; PCM; Modelling